Medicinal plant as a natural immunity booster for COVID19- A review - Patil, Anant; Kakde, Mrunmayi (Indian Journal of Integrative Medicine, 2021)
Background: The standard treatment against COVID-19 is presently lacking. It is important to suggest that people should use some supplements to boost their immune systems. The best way is to strengthen our immunity naturally with the help of medicinal plants/herbs. Objective: The objective of this review is to investigate the immunity-boosting medicinal plants c herb in support of maintaining health in the time of Corona. Methods: Pubmed and Google Scholar were searched for relevant information regarding medicinal immunity-boosting plants their uses, and properties. Results: A total of 17 articles were selected for review which included information about the immunity boosting plants and their effects on health. Conclusion: There are other certain ways to boost the ’immune system’ such as active lifestyle, physical exercise, healthy diet, relaxation, and sound sleep. Comprehensive scientific studies required to make medicinal plants available as robust medicine to fight against viral diseases like COVID-19.